Startup Weekend : how to take a company from concept to creation in 54 hours. - Nager, Marc; Nelsen, Clint; Nouyrigat, Franck (Hoboken, N.J. John Wiley & Sons, 2012)
"Tested principles for transforming an idea into a fully operational company. Startup Weekend--the organization behind 54-hour events where developers, designers, marketers, and startup enthusiasts come together to share ideas, form teams, build products, and create startups--has spawned both a global initiative in entrepreneurship as well as numerous successful startups. Startup Weekend, the book, contains best practices, lessons learned, and empowering examples derived from the organization's experiences for individuals and small organizations to follow as they launch businesses. Each of the key beliefs outlined has been tested by Startup Weekend and has yielded powerful results.The principles described in each chapter will give any business idea a greater chance for success. Chapter topics include trust and empowerment, flexible organizational structures, the power of experiential education, action-based networking, and much more Describes consequences for startup development as entrepreneurs and founders begin doing much more, even faster Profiles successful Startup Weekend companies, including two powerful examples: Memolane, an application that captures a user's online life in one timeline making it easy for users to travel back in time and relive memories; and Foodspotting, a mobile and desktop app that allows users to find and share the foods they love Apply these simple actionable principles to launch your own startup revolution"--
Keywords: Nuevas empresas comerciales; Emprendimiento